SHIFTING SOVEREIGNTIES: U.S. TARIFFS, SANCTIONS, AND SUBSIDIES AND THEIR IMPACT ON GLOBAL SOUTH AGRICULTURE AND DE-DOLLARIZATION - 1. Aejas Naik , 2 .Dr. Vinayak Pandey (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The Trump 2.0 administration’s aggressive tariffs, extraterritorial sanctions, and agricultural subsidies have profound implications for Global South nations. The U.S. dollar's role as the primary reserve currency is historically viewed for its stability and strength. The America First policies erode the said perception. This article investigates how these policies weaponize economic interdependence, destabilizing agricultural sovereignty in the Global South. It also facilitates migration towards de-dollarization. Existing research overlooks the dual pressures exerted by U.S. fiscal strategies, which simultaneously undermine food security and incentivize alternatives to dollar dependency. The study documents Global South countries move towards radical shifts in regional alliances, alternative currencies, and agro-resilience. It analyses trade disruptions caused by USA policies and the retaliatory measures by affected countries. It further examines the global ripple effects of retaliatory trade measures, inflationary shocks, and escalating debt exposure in emerging markets. This extraordinary situation may lead to recessions, particularly straining the sovereign debt of developing countries. The findings highlight that this evolving landscape necessitates enhanced South–South cooperation to protect macroeconomic stability and food security.